Position of Customary Courts in Pancasila and the 1945 Constitution - Rahmat, Doris; Saputra, Rian (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The purpose of this study is to examine the role of customary justice in Pancasila and the 1945 Constitution. The normative legal technique was employed in the research, which included numerous primary and secondary data sources such as the 1945 Constitution, regulations, legislation, court decisions, legal theories, and even scholarly opinions. The study's findings imply that Pancasila is necessary or coercive in nature. This means that anyone who is within the scope of the Unitary State of the Republic of Indonesia must respect Pancasila as a national outlook, including the State and the law itself. This means that the points of "Just and Civilized Humanity" and "social justice for all Indonesian people" which adhere to the principle of equal rights and justice must always be obeyed by all elements in the Republic of Indonesia. Pancasila is also a juridical-sociological basis, or in other words, it is the basis of norms and laws that live in society, and thus Pancasila has fulfilled the principles and basic values ​​according to the development and needs of society and the State.